I hope this helps you
x= -1 f (-1)=(-1)^2+7=1+7=8
g (f (-1))= g (8)
x=8 g (8)= 8-4/8=4/8=1/2
Answer:
The equation would be y = 3/2x + 3
Step-by-step explanation:
First we have to find the slope of the original line. We can do this by solving for y.
2x + 3y = 15
3y = -2x + 15
y = -2/3x + 5
Now that we have the slope of -2/3, we know the slope of the new line will be 3/2. This is because perpendicular lines have opposite and reciprocal slopes. We can use that and a point in point-slope form to find the equation.
y - y1 = m(x - x1)
y + 3 = 3/2(x + 4)
y + 3 = 3/2x + 6
y = 3/2x + 3
2-3(z-5)+11=4
<em>Distribute</em>
2-3z+15+11=4
<em>Move the constants to gether but make sure they keep thei signs</em>
2+15+11-3z=4
<em>Simplify</em>
28-3z=4
<em>Start to Isolate the variable by subtracting </em>28<em> from </em><u><em>both</em></u><em> sides of the equation</em>
-3z=-24
<em>Completely isolate the variable by deviding the </em><u><em>whole</em></u><em> equation by </em>-3
z=8
<u><em>If you would like anything explained, just ask</em></u>